PENGARUH MODEL PBL MENGGUNAKAN MEDIA PEMBELAJARAN AUGMENTED REALITY TERHADAP KEMAMPUAN BERFIKIR REFLEKTIF MATERI MENGUBAH BENTUK ENERGI KELAS IV SD - Widia Ayu Kusnul Khotimah; Rosmiati; Triman Juniarso; Suyitno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the fact that, in the learning process, many students remain passive and have yet to fully grasp the material. Reflective thinking skills are still relatively low, while educators continue to rely on conventional teaching models, predominantly using the lecture method. Furthermore, the learning media employed have not been fully adapted to students’ needs. The aim of this research is to determine the level of students' reflective thinking skills and their responses to these abilities. This study adopts a descriptive quantitative approach with a quasi-experimental design, involving two experimental groups treated in the same manner. The population consists of Year 4 students, divided into two classes. Data were collected through observation, pre-test and post-test assessments, and questionnaires. Based on the findings, the average score in Experimental Class 1 was 0.61, while Experimental Class 2 obtained 0.45. From this, it can be concluded that the use of the Problem-Based Learning model, incorporating Augmented Reality as a learning medium, has an impact on reflective thinking skills in the topic of energy transformation in Year 4 primary school students. The response towards reflective thinking was positive. The implementation of the Problem-Based Learning model alongside Augmented Reality proved effective in fostering a positive reflective thinking attitude. Students demonstrated great enthusiasm in learning, and their curiosity regarding various problems increased. Consequently, they were able to provide responses and solutions to issues presented within the topic of energy transformation.